Diagnostik Klinis Infeksi SARS-CoV-2 dengan Metode Apusan - Ni Luh Gede Sudaryati; Ni Luh Nyoman Vivi Tri Handayani; I Putu Sudiartawan (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
COVID-19 has become a pandemic and has caused concern for people worldwide. The rapid spread of the disease requires health care providers and health workers to be able to diagnose precisely, quickly, and accurately to speed up the stages of treatment. Reviews and procedures for implementing clinical diagnostics of SARS-CoV-2 have not been widely reported. This study aimed to analyze the differences in diagnostic procedures for COVID-19 virus infection using the smear method at the Graha Medika Clinic. Observational descriptive research was conducted in July 2022. The research took place at the Graha Medika Clinic by screening patients who took the COVID-19 examination using the smear method (antigen swab, PCR swab, and rapid antigen). The study results obtained that one (10%) out of ten people infected with COVID-19 were on the antigen swab examination. There are differences in clinical diagnostics of COVID-19 infection using the smear method, namely in the antigen swab, the test time tends to be fast compared to PCR but is somewhat less accurate; rapid antigen only detects viruses that have taken place acutely with low accuracy while PCR is used as an accurate diagnostic by identifying proteins and viral glycans molecularly, has excellent accuracy but requires experts and a long time. The clinical diagnosis of COVID-19 infection using the smear method is currently adequate. The recommended examination method for the COVID-19 examination is carried out in stages, starting from rapid antigen, antigen swab, and PCR swab. PCR swab examination is the gold standard for detecting viral genetic material.